Acute isolated partial oculomotor nerve palsy due to Lyme neuroborreliosis in a 5 year old girl. (November 2016) - Drenckhahn, Anne; Spors, Birgit; Knierim, Ellen
Abstract: Lyme neuroborreliosis is a frequent cause of facial nerve palsy in children, isolated oculomotor nerve palsy due to Borrelia-associated nervous system infection however is rarely seen. Here we report a case of isolated oculomotor nerve palsy due to a nervous system infection with Borrelia burgdorferi in childhood and restitutio in integrum after intravenous antibiotic therapy.